Study of the Tensile Damage of 321 Stainless Steel for Solar Thermal Power Generation by Acoustic Emission - Lida Liao; Qi Tan (International Journal of Photoenergy)
In this paper, the acoustic emission technique was used to study the signal during the tensile damage of 321 stainless steel for solar thermal power generation. It was found that the peak frequency can effectively distinguish different types of signals during the tensile test. The interference signals generated during the tensile test are effectively resolved by combining the amplitude-peak frequency distribution map and the energy-peak frequency distribution map. The amplitude-time map of the acoustic emission signal is successfully divided into three stages by using peak frequency parameter.